ELAC2, an Enzyme for tRNA Maturation, Plays a Role in the Cleavage of a Mature tRNA to Produce a tRNA-Derived RNA Fragment During Respiratory Syncytial Virus Infection - Choi, Eun-Jin; Wu, Wenzhe; Zhang, Ke; Lee, Inhan; Kim, In-Hoo; Lee, Yong Sun; Bao, Xiaoyong (Frontiers in Molecular Biosciences, 2021)
Respiratory syncytial virus (RSV) is the most common cause of lower respiratory tract infection in young children. However, effective treatment against RSV is unavailable. tRNA-derived RNA fragments (tRFs) are a recently discovered family of non-coding RNAs. We made an early observation that RSV infection causes significant induction of tRFs, which are mainly derived from the 5’-end of mature tRNAs (tRF5). However, their functions and biogenesis mechanism are not fully understood. Herein, we identified an enzyme responsible for the induction of a functional tRF5 derived from tRNA-Gln-CTG (tRF5-GlnCTG). We found that tRF5-GlnCTG promotes RSV replication and its induction, assessed by Northern blot and a new qRT-PCR-based method, is regulated by ribonuclease ELAC2. ELAC2-mediated tRF5 induction has never been reported. We also found that ELAC2 is associated with RSV N and NS1 proteins. Given the fact that tRF5-GlnCTG plays a role in RSV replication, the identification of ELAC2 being responsible for tRF5-GlnCTG induction could provide new insights into therapeutic strategy development against RSV infection.